Thai contemporary Music in Thai Society - Prapakdee, Chaomanat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2023)
The objectives of the study were to explore the meanings, status and cultural context of contemporary Thai music in the context of Thai society. By collecting data from documents and interviewing using popular culture concepts. The results of the study were as follows : 1) Meaning and identity of contemporary Thai music are divided into 5 meanings as follows the meaning of contemporary Thai music according to the academic principles of Western art, contemporary Thai music in the context of music history, contemporary Thai music in the dimension of controversial meaning, area and the new role of presenting, Valuable That contemporary Thai music and contemporary Thai music has a flowing meaning or no exact meaning The status of contemporary Thai music has different contexts depending on the history and purpose of the user such as being a symbol of civilization and modernity of Siam in the colonial era. It is also a tool to drive government policy and political community groups as well as represents modernity and internationality and 2) Cultural context of contemporary Thai music such as the concept of band formation, members, music instruments or materials for creating works, the concept of creating musical works, band arrangement, type of music, knowledge dissemination or skill practice, roles and public relations channel, presentation style, related person and belief system.